The psychology of women and gender half the human experience + - Else-Quest, Nicole M.; Hyde, Janet Shibley (SAGE, 2022)
"With clear, comprehensive, and cutting-edge coverage Psychology of Women and Gender +, Tenth Edition delivers an authoritative analysis of classical and up-to-the-minute research from a feminist, psychological viewpoint. The text thoroughly examines the balance of cultural and biological similarities (and differences) between the genders, noting how these characteristics may affect issues of equality as well as how men and women behave toward one another. Reflecting cutting edge developments from the field, the text puts research into context and clearly explains the relationship between gender and emotion--helping to demystify the scientific process and study of feminist psychology. It includes expansive intersectional coverage, hands-on applications, and case studies that give students further experience with key issues. This proven text equips students with a strong foundation for understanding the influences of gender, race, and ethnicity on psychology and society, as well as strategies for thinking critically about pop culture versus academic feminism as it relates to psychology"--